E-4: INVESTIGATING THE IMPACT OF BENEVOLENT LEADERSHIP ON IDIOSYNCRATIC DEALS: MEDIATING MECHANISMS OF PSYCHOLOGICAL CONTRACTS AND ROLE BREADTH SELF-EFFICACY - Ajmal, Muhammad; Islam, Azmat; Khan, Imran (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
The research posits that the psychological contract, which refers to the unwritten set of expectations between employees and their employer regarding mutual obligations and role breadth self-efficacy, denoting an individual’s belief in their capability to perform a wide array of tasks effectively, acts as critical mediating variables in the relationship between benevolent leadership and idiosyncratic deals. A benevolent leadership style, where leaders demonstrate a genuine concern and altruism towards their subordinates’ personal and professional well-being, is hypothesized to play a crucial role in facilitating idiosyncratic deals. These deals represent personalized employment arrangements that diverge from the normative organizational standards to accommodate the unique needs and aspirations of individual employees. The research is geographically situated in the Punjab province, specifically targeting the cities of Lahore, Gujranwala, and Faisalabad, and it employs a robust sample size of 400 respondents. Findings from the study reveal that benevolent leadership is significantly associated with the negotiation of idiosyncratic deals, and this relationship is intricately mediated by the strength of the psychological contract and the level of role breadth self-efficacy among employees. These results underscore the importance of benevolent leadership in fostering a supportive organizational climate that encourages the negotiation of flexible employment terms, thereby enhancing individual and organizational performance. The implications of this research are twofold. Theoretically, it enriches the existing literature on leadership styles, idiosyncratic deals, psychological contracts, and role breadth self-efficacy by delineating the mechanisms through which benevolent leadership impacts employee outcomes in the context of the banking sector. Practically, it offers valuable insights for practitioners and leaders within the banking industry of Pakistan, highlighting the significance of adopting benevolent leadership practices to cultivate a more adaptable and responsive organizational culture.